Etiquettes and ethics for the responsible herpetological collections and management - Safi, Amtyaz; Karl , Hans-Volker (SPC Journal of Environmental Sciences, 2025)
‘‘A person without ethics is a type of wild beast loosed upon this world, “Albert Camus”. “Herping” is the act of searching for rep-tiles and amphibians, usually applied to scientific data collection in the field, and for any survey procedure, they directly seek out herpetofauna. Herping is often a hands-on activity, involving the subject's capture, survey for population estimation, diversity, and photography. Being hands-on with a subject is more interactive and useful, allowing you to closely examine the animal and take detailed and beautiful photographs, which can sometimes be necessary if you plan to collect data about a species in the field. How-ever, hands-on training can introduce various negative impacts on wildlife, such as stress, habitat destruction, and even reptile dis-eases in the studied area, so responsible interactions with these animals are necessary to avoid such negative effects.